Managerial Strategy in the Implementation of the Ihfadz Method to Improve Memorization and Understanding of Nahwu in a Girls’ Islamic Boarding School - Sabila, Nanda Dini; Aini, Kuni Qur'rota; Khoiriah, Habibatul; Husain, Muhammad (MANAGIERE: Journal of Islamic Educational Management, 2026)
This study aims to analyze the managerial strategies in implementing the Ihfadz method as an integrative learning approach to improve the quality of memorization and understanding of nahwu (Arabic grammar) at Darussalam Putri Islamic Boarding School, Blokagung. A qualitative case study design was employed, utilizing participatory observation, in-depth interviews, and documentation analysis as data collection techniques. The research focused on the planning, implementation, and evaluation aspects of the Ihfadz method in teaching nadhom (structured poetic texts of grammar rules). The findings reveal that the success of the Ihfadz program is supported by systematic instructional management, active involvement of female teachers as facilitators, and continuous evaluation mechanisms. Effective managerial strategies in this method significantly contribute to both enhanced memorization and deep conceptual understanding of nahwu among students. These results offer valuable insights for developing a contextual and applicable learning management model in pesantren education that integrates memorization with comprehension.